Let's solve the equation step by step:
1) We start by removing the absolute value. We can do this by getting rid of the absolute value brackets and considering two cases: one where the expression inside the absolute value is positive and another where it is negative.
When 9-8x is positive, |9-8x| simplifies to 9-8x. The equation becomes:
9(9-8x) = 2x + 3
When 9-8x is negative, |9-8x| simplifies to -(9-8x) = -9 + 8x. The equation becomes:
9(-9+8x) = 2x + 3
2) Solving the first case:
9(9-8x) = 2x + 3
81 - 72x = 2x + 3
Combine like terms:
-72x - 2x = 3 - 81
-74x = -78
Divide both sides by -74:
x = -78 / -74
Simplify:
x = 39/37
3) Solving the second case:
9(-9+8x) = 2x + 3
-81 + 72x = 2x + 3
Combine like terms:
72x - 2x = 3 + 81
70x = 84
Divide both sides by 70:
x = 84 / 70
Simplify:
x = 6/5
4) Checking for extraneous solutions:
Let's substitute x = 39/37 and x = 6/5 back into the original equation and see if they satisfy the equation:
Case 1: x = 39/37
9|9-8(39/37)|=2(39/37)+3
9|9-312/37|=78/37+3
9|-279/37 + 312/37|=78/37+111/37
9|33/37|=189/37
9(33/37)=300/37
99/37=300/37
This statement is false, so x = 39/37 is not a solution.
Case 2: x = 6/5
9|9-8(6/5)|=2(6/5)+3
9|9-48/5|=12/5+3
9|-3/5 + 48/5|=12/5+15/5
9|45/5|=27/5
9(9)=135/5
81=135/5
This statement is also false, so x = 6/5 is not a solution.
Therefore, the equation has no valid solutions.
Solve the equation. Check for extraneous solutions. 9|9-8x|=2x+3
1 answer